2020
DOI: 10.1007/s00284-020-02063-7
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Biodegradation Ability of the Cupriavidus Genus

Abstract: The biodegradation and biodetoxification ability of five prominent mycotoxins, namely aflatoxin B1 (AFB1), ochratoxin-A (OTA), zearalenone (ZON), T-2 toxin (T-2) and deoxynivalenol (DON) of Cupriavidus genus were investigated. Biological methods are the most appropriate approach to detoxify mycotoxins. The Cupriavidus genus has resistance to heavy metals and can be found in several niches such as root nodules and aquatic environments. The genus has 17 type strains,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…We thus speculated that product A was the main degradation product, and other products could be degraded into a large number of small molecules. Earlier research [43] indicates that the toxic structure of mycotoxins often exists in the epoxy structure of toxins. Therefore, when the epoxy structure of the toxin is broken or destroyed, the toxicity of mycotoxins disappears or decreases.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…We thus speculated that product A was the main degradation product, and other products could be degraded into a large number of small molecules. Earlier research [43] indicates that the toxic structure of mycotoxins often exists in the epoxy structure of toxins. Therefore, when the epoxy structure of the toxin is broken or destroyed, the toxicity of mycotoxins disappears or decreases.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…There are studies that suggest that zearalenone can be degraded by Pseudomonas sp., Rhodococcus pyridinivorans and S. cerevisiae [15,16,17,18]. The ability of bacteria of the genus Cupriavidus to biodegradate a number of mycotoxins was revealed [19], and such as aflatoxin B1, ochratoxin A, zearalenone, T-2 toxin and deoxynivalenol were subject to study. According to the research results, seven types of strains can degrade ochratoxin A, four strains can degrade aflatoxin B1, four strains can degrade zearalenone and three strains can degrade T-2 toxin.…”
Section: Discussionmentioning
confidence: 99%
“…The SOS-chromo test showed that two strains, C. laharis and C. oxalaticus, eliminated the genotoxic effects of AFB1; however, according to the Bioluminescent Yeast Estrogen Assay (BLYES), C. basilensis reduce the estrogenic effects of ZEN. 188 Similarly, Bacillus pumilus ES-21, a soil bacteria strain was found to eliminate the ZEN in culture conditions with a biodegradation rate up to 95.7%. 189 Saccharomyces cerevisiae is one of the well-known microorganisms in food fermentation.…”
Section: Degradationmentioning
confidence: 94%
“…The degradation assay showed that Cupriavidus strains degrade OTA (97%), AFB1 (91%), ZEN (82%–96%), and T-2 (95%) toxin effectively, while none of the members could degrade DON. The SOS-chromo test showed that two strains, C. laharis and C. oxalaticus , eliminated the genotoxic effects of AFB1; however, according to the Bioluminescent Yeast Estrogen Assay (BLYES), C. basilensis reduce the estrogenic effects of ZEN . Similarly, Bacillus pumilus ES-21, a soil bacteria strain was found to eliminate the ZEN in culture conditions with a biodegradation rate up to 95.7% …”
Section: Probiotic Sources For Mycotoxin Degradationmentioning
confidence: 99%